Evaluation of molluscicidal activity of Anadenanthera colubrina extracts on adult mollusc and embryos of the species Biomphalaria glabrata (Say, 1818) - Sá, José Luís Ferreira; Siqueira, Williams Nascimento; Silva, Hianna Arely Milca Fagundes; Santos, Mariana Luiza de Oliveira; Santos, Felipe Tiago José dos; Silva, Luanna Ribeiro Santos; Cabral, Daniela Lyra de Vasconcelos; Bezerra, Isabelle Cristinne Ferraz; Soares, Luiz Alberto Lira; Melo, Ana Maria Mendonça de Albuquerque (Scientia Plena, 2016)
Schistosomiasis affects over 200 million people and a matter of concern for public health. One of the methods of combating the disease is through control of the snails of the species Biomphalaria glabrata. To evaluate the molluscicidal activity of Anadenanthera colubrina bark extract on embryos and adults of the species B. glabrata and on Artemia salina. The A. salina were exposed for 24 h to A. colubrina extract (0.125, 0.25, 0.5 and 1.0 mg/mL) diluted in sea water, while B. glabrata snails were exposed to the same period the extract (0.125, 0.25, 0.5, 0.6, 0.7 and 1.0 mg/mL) diluted in filtered and dechlorinated water. We observed that the extract at a concentration of 0.125 mg/mL showed low toxicity for A. salina used in relation to other concentrations. In the assay with B. glabrata snails were observed in adults the concentration of 0.25 mg/mL caused 80% mortality. In embryos, concentrations of 0.125; 0.25 and 0.5 mg/mL did not affect the embryo viability when compared with control group. The results show that the aqueous extract of A. colubrina demonstrated potential to be used as a biodegradable molluscicide to combat snails of the species B. glabrata.